IMPLEMENTATION OF THE TREND MOMENT METHOD IN ESTIMATING BREAD SALES - Wahyuni Siregar; Arridah Zikra Syah; Indra Ramadona Harahap (Kresnamedia Publisher, 2022)
Abstract The second strategy's pattern is a gauging technique for delivering an expected number of future bread supplies so there is no abundance or lack of stock in the upcoming month. Information on bread deals is utilized in this concentration consistently from January to December 2021. Every month's deals records are valuable for deciding if sales have expanded or diminished. The review's discoveries incorporate the improvement of an electronic framework that can create rough numbers in anticipating bargains for the next month, simplifying it to decide how much bread will be sold while considering the supply of products and how much will be delivered before very long. The following month with the objective that there is no need or overflow of bread stock. The consequences of deals forecasts for a very long time in 2021 produce expectations in January 2022, in the thirteenth period with MAD (Mean Absolute Deviation) aftereffects of 40.08% and MSE (Mean Squared Error) paces of 27.64%.